A Brief Analysis of the Teaching Practice of E-commerce - Liu, Siying (Journal of Theory and Practice of Social Science, 2023)
The 21st century has become the Internet as the center of the information age, and along with the continuous improvement of economic level, the continuous development of science and technology, e-commerce has become the country and society is very concerned about the industry, and then promote the level of teaching quality of e-commerce professional more and more attention by people. However, the actual development situation of e-commerce major is not optimistic. The teaching quality, teaching efficiency and teaching facilities matching teaching practice activities of e-commerce major are not perfect, and the construction of teaching staff in E-commerce major is not perfect, which leads to the low enrollment number of vocational colleges in E-commerce major, and the employment rate of e-commerce major is also low. The uniqueness of professional talents is not reflected, so that the teaching practice activities and teaching objectives of the whole electronic commerce major can not meet the requirements of modern society and modern enterprises for professional talents.